Consumer acceptance of biofortified iron beans in rural Rwanda: Experimental Evidence - Oparinde, Adewale; Birol, Ekin; Murekezi, Abdoul; Katsvairo, Lister; Diressie, Michael Tedla; Nkundimana, Jean d'Amour; Butare, Louis (International Food Policy Research Institute, 2015)
Iron deficiency among children and women of child-bearing age is a public health problem in many developing countries. Iron-biofortified varieties of commonly consumed staple crops have the potential to contribute to the daily iron requirements in diets. This paper examines consumer acceptance and willingness to pay (WTP) for two iron bean varieties in Rwanda: red iron bean (RIB) and white iron bean (WIB). Using the Becker-DeGroot-Marshak mechanism, the paper investigates the effect of (1) nutrition information; (2) information frame (i.e., information emphasizing loss or negative consequences of not having enough iron in diets versus information emphasizing gains or benefits of having enough iron in diets); and, (3) the frequency of providing the information on consumer WTP for iron bean varieties. Econometric models are used that take into account several issues, such as social interaction, non-payment effect, and home inventory of beans.